Kramanisasi Seks dalam Kehidupan Orang Jawa Melalui Ungkapan Tradisional - . Suwardi (Humaniora, 2009)
Javanese in their daily life, usually used traditional faithfully called kramaniasi as expression of Javanese sexuality teaching medium. The Javanese traditional utterance was naturally considered as sexuality expression medium. The expression was also a combination between semantic meanings and culture. Parents, in the etnich of Eastern ethics society (Javanese), usually gave sexual lesson using traditional utterance specifically to their daughters. The etnich expression use in Java was considered easier to teach sexual education to girl in society.